Boundaries of information property - Godt, Christine, 1964- (Cambridge : Intersentia, 2022)
This book is the result of a long-term comparative research project on intellectual property, with topics ranging from patents to copyright, examined across 16 jurisdictions. The research results question the common narratives of the distinctiveness of private and public law, of contracts and property, and of morality and the law. The fourteen selected cases, based on recent, and in some cases futuristic when the project began in 2001, scenarios, aim to identify how boundaries to information property emerge, the areas of law that are applied and the principles that are followed in order to balance the conflicting interests at stake. The issues discussed revolve around well-known interfaces such as IP and competition law, monetary interests versus personal interests in human genome data, individual freedoms-to-operate versus collective action models as found in basic research or 'creative commons'. The book shows how some national discussions appear similar on the surface, in terms of resorting to parallel principles, but subsequent domestic policy answers vary greatly. Even legislation which aims at harmonisation may result into more diversity. The national reports in Part III are complemented by comparative analyses by the editors, whilst the chapters in Part II are dedicated to an analysis of the submissions from a theoretical point of view, departing from the editors' own research interests. The chapter in Part I describes the overall 'Common Core' research method, which splits the national reports into operative, descriptive and metalegal formants.
Title from publisher's bibliographic system (viewed on 16 Dec 2022).
Keywords: Intellectual property -- Europe